Peran Media Sosial dalam Pemasaran Produk UMKM di Desa Ngunut Parang Magetan (Studi Kasus pada UMKM Cake dan Frozen Food) - Daroji, Choirul; Nurdiantini, Faisa; Fuadah, Tsamrotul; Sari, Widya Purnama (Civiliza Publishing, 2024)
Ngunut Village is one of the villages located in Parang District which is a place for group 21 community service courses (KPM). Ngunut Village has several resources that can be developed, either in the form of Natural Resources or Human Resources. Several strengths or assets in Ngunut Village have been found, one of which is regarding the village's natural potential which can be utilized to the fullest by making the community the main actor and determinant of Development Efforts. Therefore, with this community service activity the author tries to develop a marketing strategy to increase MSME income. So that MSME actors can be more creative and innovative in planning successful marketing strategies. Now it is a must to have a presence on social media considering its significant influence, an MSMEs can develop faster by having social media for promotion and sales compared to not using it. The purpose of this study was to measure the role of social media as a promotional tool in increasing product marketing from MSMEs that focus on the cake and frozen food business in Ngunut Village, Parang District, Magetan Regency. The method used in this research is the ABCD (Assets Based Community Development) approach, namely identifying the assets owned by the surrounding community. The results of the study show that according to the informants involved, the use of social media as a promotional tool has a very important role in increasing product marketing from MSMEs engaged in the culinary field, especially for small businesses.